Mapping preferences for the number of built elements. Issue 1 (3rd April 2018) - Hussein, Dheyaa; Sarkar, Somwrita; Armstrong, Peter
Abstract : Purpose: The purpose of this paper is to investigate the relationship between the number of design elements in the context of building facades in urban streetscapes and visual preferences of users to enable a more meaningful citizen participation in the design of local streetscapes. Design/methodology/approach: This paper developed a web application, which manages experiments through programmatically creating scenes and displaying them online to participants using questionnaires. It collects preferences towards the number of design elements in the scenes and determines the statistical relationship between them. Findings: The results offer an empirical description of a semi-convex relationship between the number of elements and preferences. They confirm that participants from a particular area inter-subjectively agree in their visual judgements towards the number of design elements, and justify the employment of a regression model fitted on the preferences of residents to assess design proposal in their area. Originality/value: The paper offers an empirical description of the relationships between preferences and a wide range of values of the number of design elements and empirically supports that people from one area inter-subjectively agree in their judgements towards a visual aspect of the building facades. The study introduces a new analytical component, known as the vertex, which could alter future methods on the visual evaluation of the built environment.